The Mechanization of Monitoring Students’ Study Rights in Secondary Schools - A. K. Kadrekova (International Journal on Integrated Education, 2021)
The article presents the results of monitoring of children's rights, the role of teachers in ensuring the well-being of children, "child", "child rights" and the National Center for Human Rights in educational institutions.